Optimalisasi Artificial Intelligent (Ai) dalam Pemberdayaan Ekonomi Kreatif Umat Melalui Pengembangan Potensi Produk Halal - Akbar, Mochamad Malik; Meirani, Nadia; Taufik, Rezi Muhamad; Tresna, Eka (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
Entrepreneurship is a strategic issue in community service due to its role in reducing unemployment and promoting innovation-driven economic growth. Universitas Islam Bandung, through the Management Study Program, implemented the Entrepreneurship Development Program (PPK) to address students’ low entrepreneurial interest and readiness. Designed with a participatory and collaborative approach, the program involved students actively in recruitment, training, and intensive business mentoring. A distinctive feature of this program was the integration of artificial intelligence (AI) as a supporting tool. Applications such as ChatGPT and Bard were used for market research and business idea validation, while Canva, Pictory.ai, and Gamma.app supported digital content creation to enhance branding and customer engagement. The program achieved notable results: all participating tenants successfully obtained business legality (NIB and certification), produced intellectual property-protected products, and published scientific articles with media exposure. The initiative was further strengthened by collaboration with HIPMI PT, contributing to the development of a campus-based entrepreneurial ecosystem. These outcomes demonstrate that a practice-based approach combined with continuous mentoring is effective in improving students’ entrepreneurial motivation, readiness, and intention, while also supporting the achievement of key performance indicators at the university level.